Extending Employee Protections to Gig-Economy Workers Through the Entrepreneurial Opportunity Test of Fedex Home Delivery - Peter Gibbins (Washington University Journal of Law & Policy, 2018)
This note by Peter Gibbins explores the legal challenges both companies and workers face in the “gig-economy” – the digital marketplace of companies like Uber, Lyft, Taskrabbit, and more. Specifically, Gibbins highlights the problems inherent in classifying workers as “independent contractors” as opposed to employees. The classification of “independent contractor” significantly limits the rights and protections workers receive, while providing companies flexibility and increased savings by reducing or eliminating employee benefits. While unionization may help workers negotiate better working conditions, pay, and benefits, independent contractors attempting to organize face significant legal hurdles under the National Labor Relations Act and antitrust laws. Gibbins argues that extending NLRA protections to gig-economy workers is essential to sustain the new gig-economy, and that tests already utilized by courts ought to allow protections for some gig-economy workers.
Keywords: gig-economy; Uber; Lyft; Taskrabbit; Postmates; National Labor Relations Act; NLRA; unions; collective bargaining; antitrust; employment law; independent contractor; employee; worker classification; benefits; employer/employee relationship